Unique Localization of Bovine Viral Diarrhea Virus Non-Structural NS4B Protein in Infected Cells - Suda, Yuto; Yamane, Daisuke; Atif Zahoor, Muhammad; Mohamed, Yassir Mahgoub; Murakami, Shin; Kato, Kentaro; Horimoto, Taisuke; Akashi, Hiroomi (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
Bovine viral diarrhea virus (BVDV), an important pathogen infecting ruminants, has 2 biotypes: cytopathic (cp) and noncytopathic (ncp), which are related to the onset of disease. The viral replication complex is composed of viral non-structural (NS) proteins, raising the possibility that NS protein(s) play a role in viral biotypes. To gain insight into this possible role, we analysed the intracellular localization of each NS protein in both cp and ncp virus-infected cells, and found that NS4B protein, a possible anchor protein of the viral replication complex, showed a unique dotted localization pattern that markedly merged with an endoplasmic reticulum marker, unlike other NS proteins, although there was no difference in the localization of NS4B protein between the 2 biotypes.Â